Improving Knowledge, Attitudes and Skills of Wani Ngandani Cadres on Effective Communication Dissemination of Health Protocols and Continuous Monitoring (Surveillance) for Covid 19 Management in Surabaya - Shrimarti Rukmini Devy; Sri Widati; Mochammad Bagus Qomaruddin; Muji Sulistyowati; Oedojo Soedirham; Santi Martini; Atik Choirul Hidajah; Isma Faridatus Sholihah; Dayu Marista; Alfi Makrifatul Azizah; Eni Purwaningsih (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2022)
Background: COVID-19 preventive behavior plays a role in reducing infection rates and controlling the spread of the disease. In order to optimize the behavior of preventing COVID-19 in the Pacar Keling Sub-district, Tambaksari District, a health promotion program is needed by involving the active participation of the community, so that the community is able to overcome health problems with their existing potential. Objectives: This study aimed to determine the increase before and after being given knowledge and skills on how to communicate effectively when socializing the 5M health protocol, planning and evaluating in conducting socialization activities and how to carry out continuous surveillance on Wani Ngandani cadres as well as increasing knowledge related to health protocols during the COVID-19 pandemic for webinars. Methods: In each activity, 1-3 and RTL Webinar, Pre-test, and Post-test data are collected to measure the level of knowledge of participants. A paired t-test is used as the data analysis to determine the difference before and after being given training. The methods applied in measuring cadre skills are presentation and role play. Meanwhile, RTL activities are held online in the form of Community Service Webinars. The materials provided in training activities 1-3 are in the form of PPT materials and manuals. Results: Based on the results of the paired t-test, it is known that there were significant differences (sig <0.05) in the results of the pre-test and post-test on the four training activities. Conclusion: This program was effective and its implementation has succeeded in achieving the expected target and there has been a strengthening of knowledge in the community.